Effects of the Skills4Genius sports-based training program in creative behavior - Santos, S.; Jimenez, S.; Sampaio, J.; Leite, N. (PLOS ONE, 2017)
Team Sports has been suggested as a suitable environment to investigate creative behavior. This study`s purpose was two-fold: first, it intended to identify the effects of the Skills4Genius sports-bases training program in thinking, motor, and in-game creative behavior in team sports. Second, it aimed to investigate the relationship between creative thinking and in-game creativity. Forty children from primary school were allocated into control (n = 18, age: 9.2±0.4) and experimental (n = 22, age: 9.5±0.7) groups. The experimental group participated in a five-month training program involving either creative thinking, diversification, physical literacy, and nonlinear pedagogy approaches (Skills4Genius). Variables in the study included: a) creative thinking; b) motor performance (vertical jump, speed, and agility); c) in-game individual creative behavior (attempts, fluency, and versatility); and d) in-game collective behavior (positional regularity). The results suggested that the Skills4Genius program fostered creative thinking, agility, and speed performance. Moreover, it stretched the in-game individual creative behavior mainly through the improvement of the attempts and versatility of the player`s actions. Lastly, it nurtured a better learning of the tactical principles, whereas the children were more coordinated with their teammates` and opponents` positioning. Additionally, this study presents a positive correlation linking creative thinking and in-game creative performance. These findings highlighted that creativity is facilitated while players become more thinking and game-skilled. Coaches and educators may apply this functional environment to inspire children`s disposition to move outside the box and trigger a creative spark in team sports players. Notwithstanding, the sports environment is ideally suited for fostering creative behavior, a higher-order disposition that will go on to differentiate the everyday life of a child.